The first in situ electron temperature and density measurements of the Martian nightside ionosphere. Issue 21 (5th November 2015) - Fowler, C. M.; Andersson, L.; Ergun, R. E.; Morooka, M.; Delory, G.; Andrews, D. J.; Lillis, Robert J.; McEnulty, T.; Weber, T. D.; Chamandy, T. M.; Eriksson, A. I.; Mitchell, D. L.; et al.
Abstract: The first in situ nightside electron density and temperature profiles at Mars are presented as functions of altitude and local time (LT) from the Langmuir Probe and Waves (LPW) instrument on board the Mars Atmosphere and Volatile EvolutioN (MAVEN) mission spacecraft. LPW is able to measure densities as low as ∼100  cm − 3, a factor of up to 10 or greater improvement over previous measurements. Above 200 km, near‐vertical density profiles of a few hundred cubic centimeters were observed for almost all nightside LT, with the lowest densities and highest temperatures observed postmidnight. Density peaks of a few thousand cubic centimeters were observed below 200 km at all nightside LT. The lowest temperatures were observed below 180 km and approach the neutral atmospheric temperature. One‐dimensional modeling demonstrates that precipitating electrons were able to sustain the observed nightside ionospheric densities below 200 km. Key Points: First in situ nightside electron density and temperature profiles on the nightside of Mars Electron temperatures approach neutral atmospheric temperatures below  200 km Electron densities below 200 km require additional ionization source